2019
DOI: 10.1063/1.5129533
|View full text |Cite
|
Sign up to set email alerts
|

A step in the direction of resolving the paradox of Perdew-Zunger self-interaction correction

Abstract: Self-interaction (SI) error, which results when exchange-correlation contributions to the total energy are approximated, limits the reliability of many density functional approximations. The Perdew-Zunger SI correction (PZSIC), when applied in conjunction with the local spin density approximation (LSDA), improves the description of many properties, but overall, this improvement is limited. Here we propose a modification to PZSIC that uses an iso-orbital indicator to identify regions where local SI corrections … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 104 publications
4
104
0
Order By: Relevance
“…More generally, for nonmetals (including water), any large error of SCAN is dominated by self-interaction. Improvements in the way the SIE is handled are under development (46)(47)(48), but here we will apply only a currently standard way.…”
mentioning
confidence: 99%
“…More generally, for nonmetals (including water), any large error of SCAN is dominated by self-interaction. Improvements in the way the SIE is handled are under development (46)(47)(48), but here we will apply only a currently standard way.…”
mentioning
confidence: 99%
“…Recent work has shown that the Perdew-Zunger selfinteraction correction (PZ SIC), which makes any approximate density functional exact for non-overlapped one-electron densities, introduces errors of as much as 6% in the large-Z or slowly-varying-density limit [20], and that these errors can degrade the predicted equilibrium properties of molecules. Carefully scaling down the PZ SIC correction to zero in slowly-varying regions yields much better results [21,22]. The LYP correlation functional is highly accurate for first and second row molecules, but highly inaccurate for the uniform gas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work [20][21][22] has shown that errors of even a few percent in the uniform-density limit can seriously undermine the accuracy of approximate density functionals for the equilibrium properties of atoms and small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches have been proposed to remove the SIEs. 7,[9][10][11][12][13][14][15][16] In this work, we focus on the most widely used self-interaction-correction, developed by Perdew and Zunger (PZ-SIC) 7 , which has been used to study atoms, molecules, and solids. 8,13,14, A. Perdew-Zunger Self-interaction-correction (PZ-SIC)…”
Section: Introductionmentioning
confidence: 99%